2001
DOI: 10.1103/physreve.63.026402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of harmonic generation from solid surfaces irradiated by multipicosecond laser pulses

Abstract: An experimental study is presented on harmonic generation from solid surfaces using 27 ps Nd:glass laser pulses (lambda=1053 nm) in the intensity range of 10(13)-10(15) W cm(-2). Second, third, and fourth harmonics emitted in the specular reflection direction showed intensity scaling exponents of 1.5, 1.8, and 3.8 for an obliquely incident p-polarized laser beam, providing a conversion efficiency of 2x10(-8), 10(-10), and 5x10(-12) at 10(15) W cm(-2), respectively. Second and third harmonic radiation generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…It was observed that harmonics were generated by both p-and s-polarizations of laser in non-relativistic limit, contradictory to the theoretical expectation. The observed anomaly was explained in terms of the role of Faraday rotation of laser polarization through self-generated magnetic field in plasma [30].…”
Section: Early Studies Of Harmonics From Solid Surfacesmentioning
confidence: 87%
See 2 more Smart Citations
“…It was observed that harmonics were generated by both p-and s-polarizations of laser in non-relativistic limit, contradictory to the theoretical expectation. The observed anomaly was explained in terms of the role of Faraday rotation of laser polarization through self-generated magnetic field in plasma [30].…”
Section: Early Studies Of Harmonics From Solid Surfacesmentioning
confidence: 87%
“…Norreys et al [29] have observed harmonic emission up-to 75th order with a 1,053 nm, 2.5 ps Nd:glass laser. Ganeev et al [30] have observed high-order harmonic emission from the solid surfaces using 27 ps Nd:glass laser pulses. It was observed that harmonics were generated by both p-and s-polarizations of laser in non-relativistic limit, contradictory to the theoretical expectation.…”
Section: Early Studies Of Harmonics From Solid Surfacesmentioning
confidence: 98%
See 1 more Smart Citation
“…Schifano et al [17] have observed the second harmonic generation from preformed plasma as a valuable diagnostic for fi lamentation under various interaction conditions. Ganeev et al [18] have presented experimental study on harmonic generation from solid surface irradiated by short laser pulses. The relative harmonic yield for the P and S polarization of the pump wave and their scaling with laser intensity are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…At this laser intensity, the space resolved measurements show that the spectral intensity of this line peaks at ∼1.5 mm from the target surface indicating the maximum population of C 5+ ions (n = 3), at this distance. From a comparison of spatial intensity variation of this line with that of C 5+ Ly-α (n = 2 → 1) line, it is inferred that n = 3 state of C 5+ ions is predominantly populated through three-body recombination pumping of C 6+ ions of the expanding plasma consistent with quantitative estimates on recombination rates of different processes.Intense xuv soft X-ray radiation from pulsed laser plasma sources is of current interest for a variety of research investigations and technological applications [1][2][3][4][5]. Measurements of xuv radiation spectrum of laser-produced plasmas with high spectral, temporal and spatial resolutions is an essential part of many studies of laser plasma interaction, particularly for investigations of xuv soft X-ray lasing schemes [6].…”
mentioning
confidence: 99%